DESAIN PERKULIAHAN BAHASA ARAB MELALUI GOOGLE CLASSROOM - Rozak, Abd.; Albantani, Azkia Muharom (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
In this modern day, the number of different ways of learning in addition to being in the classroom, one of them is learning through Google Classroom. This type of research was a qualitative research in the form of field research. Arabic lectures were conducted by using Google Classroom media and administrated by six different classes in non-language study program environments. This study showed that this application can help and facilitate the lecturers and students in carrying out the learning process in depth. This was because both students and lecturers can collect the assignments, distribute the assignments, and assess the assignments at home or anywhere without being bound by time limits or hours of study.